Suppressive effect of syndecan ectodomains and N-desulfated heparins on osteoclastogenesis via direct binding to macrophage-colony stimulating factor. Issue 11 (November 2018) - Kim, Jin-Man; Lee, Kyunghee; Kim, Mi; Shin, Hong-In; Jeong, Daewon
Abstract Syndecans, a family of cell surface heparan sulfate proteoglycans, regulate cell differentiation via binding of their heparan sulfate chains to growth factors and cytokines and play a role in tumor growth and progression, wound repair, and intestinal mucosal damage. However, the functional and mechanistic roles of syndecans in osteoclast differentiation and bone metabolism are yet unclear. Here, we demonstrated that post-translationally glycosylated ectodomains of syndecan-1 to 4 obtained from mammalian cells efficiently suppressed osteoclast differentiation compared to those obtained fromEscherichia coli with no systems for glycosylation. A concomitant decrease in the expression of osteoclast markers such as nuclear factor of activated T cells 1 (NFATc1), c-Fos, and ATP6V0D2 was observed. In addition, heparan sulfate and selectivelyN -desulfated heparin derivatives with 2-O- and 6-O-sulfate groups and no anticoagulant activity in blood inhibited osteoclast differentiation. The inhibitory effects of syndecan ectodomains, heparan sulfate, andN -desulfated heparin derivatives on osteoclast differentiation were attributed to their direct binding to the macrophage-colony stimulating factor (M-CSF), resulting in the blocking of M-CSF-mediated downstream signals such as extracellular signal-regulated kinase (ERK), c-JUN N-terminal kinase (JNK), p38, and Akt. Furthermore, mice injected with syndecan ectodomains, heparan sulfate, andN -desulfated heparin derivatives into periosteal regions of calvaria showed reduction in the formation of tartrate-resistant acid phosphatase (TRAP)-positive mature osteoclasts on the calvarial bone surface, thereby exhibiting decreased bone resorption. Together, these results revealed a novel role of heparan sulfate chains of syndecan ectodomains in the regulation of osteoclast differentiation.